Detecção de MYCOPLASMA SP. por PCR para controle de qualidade de imunobiológicos, determinação de concentrações de MYCOPLASMA SP. que afetam culturas celulares e avaliação da filtração na eliminação destes contaminantes - Netto, Cristiane (2013)
The genus Mycoplasma belongs to the class Mollicutes and it is the smaller prokaryotes (0,3 to 0,8 µm). They are distributed in the nature as humans’, mammals’, reptiles’, fishes’, arthropods’ and plants’ parasites. Its capacity of provoking alterations in cellular cultures evidences the complex and singular character of such organisms to cause prejudices to the biotechnological industry. The immunobiological production needs two essential products, which are the bovine fetal serum or the bovine serum and the cellular cultures. In order to control the quality of such inputs in the industry, the evaluation of the presence or of the absence of mycoplasma and the determination of the effect that it can cause in cellular cultivations is fundamental. The scopes of the work herein is evaluate if the Polymerase Chain Reaction (PCR) could be used as a control quality tool, evaluate the mycoplasma concentrations capable to affect the cellular growth and evaluate the mycoplasma elimination through filtration in 0.1 µm pores. In order to reach such scopes, four species of Mycoplasma were selected (M. orale, M. salivarium, M. arginine and M. hyorhinis) and the cultivation in broth and in agar SP4 was performed. To implement the PCR technique, two DNA extraction methods (phenol/chloroform and boiling) were used and the sense GPO-3 and the antisense MGSO primers were selected. After the evaluation of the sensitivity and of the specificity, the methodology was challenged through the research of mycoplasma in bovine sera and in cells BHK21. It was observed that 56.5% of bovine sera and 15.2% of cells BHK21 cultures evaluated were contaminated by mycoplasma. The both experimental contamination tests with cells BHK21 and Vero with serial dilutions of M. orale, M. salivarium, M. arginine and M. hyorhinis and the evaluation of the filtration efficacy at 0.1 µm were determined through the absorbance measuring and the cellular growth reduction percentage evaluation. The first contamination test occurred after 24 hours of cells incubation and the second one, since the zero time with 48 hours of incubation. It was observed that the cells Vero suffered higher cytopathic effects than the BHK21 ones in the both tests performed with the same concentrations of the used strains. The growth of the both cellular cultivation strains was affected in comparison to the control one, especially during the first dilutions. Thus, the severity of the cytopathic effect depends on the mycoplasma specie, on the strain concentration and on the time of contact with the cellular culture. The elimination of mycoplasma through filtration at 0.1 µm was efficient for low concentrations of such microorganisms due to the verification of cytopathic effects in cultivations of the cells BHK21 and Vero with high concentrations of mycoplasmas and due to the amplification of the mycoplasma specific DNA fragment.